2021
DOI: 10.1192/j.eurpsy.2021.2246
|View full text |Cite
|
Sign up to set email alerts
|

Proportion and predictors of remission and recovery in first-episode psychosis: Systematic review and meta-analysis

Abstract: Background To determine the proportion of patients in symptomatic remission and recovery following a first-episode of psychosis (FEP). Methods A multistep literature search using the Web of Science database, Cochrane Central Register of Reviews, Ovid/PsychINFO, and trial registries from database inception to November 5, 2020, was performed. Cohort studies and randomized control trials (RCT) investigating the proportion of remission and recovery following a FEP were included. Two independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 73 publications
4
20
0
Order By: Relevance
“…The statistically significant differences in premorbid adjustment, early illness features, and baseline clinical characteristics between the groups are consistent with previously identified predictors of long-term outcome [14, 29, 61] and, more specifically, longer-term CR and TR [10, 14, 16, 18]. This supports the validity of the identified outcome groups as early indicators of long-term outcomes [1, 2, 4, 62]. That a schizophrenia diagnosis per se did not have an individual contribution in the regression model shows that the underlying differences are not secondary but integral to the diagnosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The statistically significant differences in premorbid adjustment, early illness features, and baseline clinical characteristics between the groups are consistent with previously identified predictors of long-term outcome [14, 29, 61] and, more specifically, longer-term CR and TR [10, 14, 16, 18]. This supports the validity of the identified outcome groups as early indicators of long-term outcomes [1, 2, 4, 62]. That a schizophrenia diagnosis per se did not have an individual contribution in the regression model shows that the underlying differences are not secondary but integral to the diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…The outcome trajectories of individual patients are difficult to predict. Accumulating evidence, however, indicates that clinical development over the first years of treatment is critical for longer-term outcomes [4][5][6]. Identifying early indicators of treatment response is thus essential to avoid prolonged exposure to ineffective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Following their publication, the RSWG-cr have been widely employed to de ne remission in psychotic disorders (14). A recent meta-analysis of longitudinal studies of rst-episode psychosis found a 52% remission frequency over four years when using RSWG-cr, although the heterogeneity between studies was high (15). Symptomatic remission is considered a necessary step towards wider recovery, which also includes psychosocial functioning and well-being (10).…”
Section: De Nition Of Remission In Psychotic Disordersmentioning
confidence: 99%
“…Data were collected online by screening a nationwide panel of survey participants in November 2021. The inclusion criteria were family members who (1) were aged between 18 and 74 years; (2) had patients diagnosed with schizophrenia or schizoaffective disorder; (3) were patients' siblings; (4) had patients being treated through regular visits, having had their last visit to a medical facility within the past year, or having been admitted to a medical facility within the past year; and (5) had patients aged between 16 and 74 years. We excluded family members who (1) had patients with depression or bipolar disorder, (2) were patients' parents or spouses, and (3) had patients who had their last visit to a medical facility over a year ago or were on an unknown treatment regimen.…”
Section: Data Collectionmentioning
confidence: 99%